Reimagining and radicalizing community development practice in south-east Queensland through popular education action research. (3rd May 2019) - Lathouras, Athena; Westoby, Peter; Shevellar, Lynda
Abstract: This article analyses the ways community development in Australia has succumbed to neoliberal forces resulting in conservative or reformist practice. Ledwith ( Community Development in Action: Putting Freire into Practice, 2015, Policy Press, UK.) argues that popular education theory is a useful vehicle through which community development can recover its emancipatory intentions and take on a more critical role in strategising and acting for structural changes. This article reports on a participatory action research project undertaken in Australia in 2017, to explore what the Popular Education tradition could bring to the field of community development within south-east Queensland. The research aim was to theory-test the possibilities of popular education for influencing contemporary community development in an era of hegemonic service-delivery and welfare work within Australia. Practitioners were exposed to a series of popular education workshops, grounding a clear experiential model for taking theory into action that can advance social justice agendas and further their work. Findings from the project reveal that it is possible to stimulate thinking about radical practice with popular education theory. Moreover, exploration of the theory needs forums and communities of practice for collective critical reflection. Such processes provide both theoretical knowledge and collegial support for practitioners to experiment with actions in line with the radical tradition, and thus develop a radical praxis to resist the worst elements of neoliberalism.